TEACHER PERSONALITY ON PUPILS’ PERFORMANCE IN LITERATURE IN ENGLISH IN BULAWAYO METROPOLITAN PROVINCE - Nhlanhla, Mpofu; Thubelihle, Sithole (European Scientific Journal, ESJ, 2014)
This research aimed at determining if there is a relationship between teacher personality and pupil performance in Literature in English. The research was conducted using the quantitative design. A population of 37 teachers was used from the Bulawayo Metropolitan district. The 37 teachers were ‘O’ Level Literature in English. The sample used was 10 teachers from the population. A standard personality test and learners’ performance records in Literature in English were used to collect data. Data was analysed using Statistical Package for Social Sciences (SPSS). The research questions were analysed using descriptive and regression analysis. The findings show that pupils’ performance in Literature in English in Bulawayo Metropolitan District is at 65, 90%. The phlegmatic temperament is the most common personality followed by the choleric, the melancholic and the sanguine had the least representation among the Literature in English teachers. The results also showed that there was a positive relationship between teacher personality and pupil performance. It was revealed that 3.8 % of the time teacher personality affects pupil performance.